2017
DOI: 10.3390/ma10020197
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2D Nitrogen-Doped Mesoporous Carbon Catalyst for Oxygen Reduction Reaction

Abstract: 2D nitrogen-doped mesoporous carbon (NMC) is synthesized by using a mesoporous silica film as hard template, which is then investigated as a non-precious metal catalyst for the oxygen reduction reaction (ORR). The effect of the synthesis conditions on the silica template and carbon is extensively investigated. In this work, we employ dual templates—viz. graphene oxide and triblock copolymer F127—to control the textural features of a 2D silica film. The silica is then used as a template to direct the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The multipoint BET nitrogen adsorption-desorption isotherms for the two different carbon supports (Vulcan and Vinatech carbons) before and after deposition were obtained to systemically reveal the effect of the textural properties on the growth mechanism of the Pt NPs produced by FBR-ALD. The isotherms of all the samples showed type IV characteristics with an H3 hysteresis loop 42 (Fig. 1b), which was attributed to the presence of slit-like mesopores.…”
Section: Carbon Surface Characteristicsmentioning
confidence: 94%
“…The multipoint BET nitrogen adsorption-desorption isotherms for the two different carbon supports (Vulcan and Vinatech carbons) before and after deposition were obtained to systemically reveal the effect of the textural properties on the growth mechanism of the Pt NPs produced by FBR-ALD. The isotherms of all the samples showed type IV characteristics with an H3 hysteresis loop 42 (Fig. 1b), which was attributed to the presence of slit-like mesopores.…”
Section: Carbon Surface Characteristicsmentioning
confidence: 94%
“…Research into catalysts based on formulations free of platinum group metals (PGMs) is gaining increasing interest within the scientific community due to the attractive possibility of substituting expensive precious metals with more economical, available, and green catalytic materials [ 9 ]. Yu et al reported the synthesis of nitrogen-doped mesoporous carbon for the ORR [ 10 ]. Their investigation covers the effect of a set of synthesis conditions of interest, and how these influence the physico-chemical features of nitrogen-doped carbons, together with the evaluation of ORR activity in an alkaline environment using a rotating disk electrode.…”
Section: This Special Issuementioning
confidence: 99%
“…Wei et al reported a hierarchically tubular nitrogen‐doped carbon structure using Cu 2 O nanowires as sacrificial templates 27 . Yu et al employed a dual templates method, in which GO and triblock copolymer F127 were used to control the character of silica and the silica was then used as the second template to synthesize the catalyst 28 . Chen et al obtained a nitrogen‐doped CNT with a large specific surface area owing to the in situ MgO template method 22 .…”
Section: Introductionmentioning
confidence: 99%